Batch reverse osmosis : modelling and experiments to study permeate quality - Koo, Kwan Yee (2019)
As water scarcity continues to worsen worldwide, it is imperative to establish cost-effective ways of producing freshwater to match the ever-growing demand. Among alternative water treatment technologies that have improved freshwater availability, desalination remains the most energy-intensive and costly option. The most widely used desalination technology is continuous reverse osmosis (RO). The conventional continuous RO process consumes excess energy because high pressure is applied where it is not needed. One way to mitigate this excess is through multi-staging. Theoretically, a system with infinite stages would be able to apply feed pressures matching the rise in salt concentration. Batch RO can actualize this concept, only that the stages exist in time rather than space. Previous work has shown that batch RO can still offer energy savings despite its inefficiencies, hence the next step in evaluating its viability is to examine the permeate quality. In this project, a model involving all phases in the batch RO operation, alongside salt passage and osmotic backwash, was developed to predict permeate quality. Experiments were also conducted to test a hypothesis relating permeate flux and average permeate concentration. The model has produced results in line with expected trends, and the experiments support the hypothesis. Overall, the batch RO permeate quality is found to be within range of global standards.